228 Factors Associated with Constipation in A Pediatric Intensive Care Unit. (October 2012) - Lopez, J; Gonzalez, R; Urbano, J; Solana, MJ; Botran, M; Garcia, A; Lopez-Herce, J
Abstract : Backgrounds and aims: Constipation is a frequent complication in critically ill patients although there are few studies in children. Methods: Prospective observational study with children admitted in the PICU for more than 3 days. PRISM, PELOD and PIM2 scores, total number of days with mechanical ventilation, duration and doses of sedatives and inotropes, and nutritional aims were recorded. Correlations between these parameters and time to first defecation were analyzed. Results: 84 children (median 13 months-old) were included. Mean time to first defecation was 4 days (range 0–19). A positive correlation with PRIMS (r:0.39), PELOD (r:0.33) and PIM2 (r:0.48) scores (p<0.01) was observed. Moderate correlation existed between the time to first defecation with the administration of vecuronium (r:0.40 p<0.01) and the days without enteral feeding (r: 0.46 p<0.01). There was a low correlation with days of mechanical ventilation (r:0.3 p<0.01), treatment with fentanyl (r:0.23 p<0.05), remifentanyl (r:0.25 p<0.05), and absolute and proportional gastric residual volume (r:0.24 p<0.05 and r:0.3 p<0.01, respectively). A negative association with daily enteral feeding volume (r:-0.37 p<0.01) was observed. Treatment with epinephrine or norepinephrine was also associated with a delay in the first defecation (5.6 vs 2.8 days p<0.01). Conclusions: Mean time to first defecation in critically ill children is 4 days. Constipation in critically ill children seems to be associated with severity of illness. Enteral nutrition could help bowel motility.